2018
DOI: 10.1007/s40263-018-0506-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Glutamate NMDA Receptor Antagonist Memantine as Adjunctive Treatment in Borderline Personality Disorder: An Exploratory, Randomised, Double-Blind, Placebo-Controlled Trial

Abstract: Memantine at a 20-mg daily dose is a well tolerated drug that can improve BPD symptomatology and may be a promising novel therapeutic for its treatment. Further studies are needed to explore the efficacy of memantine versus placebo, as well as in comparison with other potential treatments for BPD. ClinicalTrials.gov identifier: NCT02097706.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…Its off-label use in the treatment of BPD is supported by the hypothesis of glutamate dysregulation and excitotoxicity of BPD core symptoms [ 103 ]. To date, only a double-blind placebo-controlled RCT showed that a dose of 20 mg of memantine per day added on to another usual drug treatment was well tolerated and improved BPD symptoms [ 104 ]. Given the existence of only one study, further research is needed to assess the efficacy of memantine compared to placebo and other treatments in patients with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…Its off-label use in the treatment of BPD is supported by the hypothesis of glutamate dysregulation and excitotoxicity of BPD core symptoms [ 103 ]. To date, only a double-blind placebo-controlled RCT showed that a dose of 20 mg of memantine per day added on to another usual drug treatment was well tolerated and improved BPD symptoms [ 104 ]. Given the existence of only one study, further research is needed to assess the efficacy of memantine compared to placebo and other treatments in patients with BPD.…”
Section: Discussionmentioning
confidence: 99%
“…From this review, novel agents have been tested for efficacy in treating not PIA but related conditions such as anger, hostility, and irritability. Such agents include 5-aminolevulinic acid phosphatase ( Higashikawa et al, 2020 ), fish oil ( Dean et al, 2014 ), and specific omega-3-fatty acids ( Bellino et al, 2013 ), the 5-HT 2c agonist lorcaserin ( Coccaro and Lee, 2019 ), the antiepileptic tiagabine ( Gowin et al, 2012 ), the benzodiazepine clobazam tested in Lennox–Gastaut Syndrome ( Paolicchi et al, 2015 ), and the glutamate NMDA receptor antagonist memantine ( Kulkarni et al, 2018 ). As an antagonist for neurokinin-1 (NK1) receptors upon which substance P acts, aprepitant, used as an antiemetic, could theoretically function as an AIAA but has yet to be tested ( Fanning et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…As an NMDA receptor antagonist, it is thought that memantine can slow or halt the constant NMDA activation that is brought about by excessive glutamate release at the postsynaptic receptor site (Stahl et al, 2018). Neuronal toxicity is present with excessive glutamate; it is hypothesized that the blockade of excessive glutamate that memantine provides slows cognitive loss in ASD and AD patients (Kulkarni et al, 2018). Memantine is approved for use in moderate to severe AD, and also used off label in mild AD and other memory and cognitive disorders (Stahl et al, 2018).…”
Section: Memantinementioning
confidence: 99%